STUDI KASUS PENGARUH YOUTUBE TERHADAP ANAK YANG MENGALAMI SPEECH DELAY DI SLB HARAPAN MULIA - Muhammad Raihan Siregar; Nelyahardi Nelyahardi; Muhammad Zulfikar (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
This research aims to find out the influence of YouTube on children who experience speech delay at Harapan Mulia Special School. This research is qualitative with descriptive method, involving one teacher and two parents of two students as informants. Data were analyzed through interviews, observation, and documentation, with data validity tested using source triangulation. The results showed that YouTube affects MEE children who experience speech delay, making their speech development impaired because it is difficult to concentrate and communicate. The child prefers to be alone and watch YouTube rather than interact. Teachers at SLB Harapan Mulia handle speech delay with various stimuli to encourage socialization, and evaluate the child's development after therapy. The effect of YouTube on elementary school children with speech delay also shows that frequent YouTube viewing inhibits their language skills and vocabulary. These children are shy to speak in front of friends and are less responsive when spoken to. Teachers at SLB Harapan Mulia educate parents on the importance of monitoring the duration, frequency and type of YouTube viewing, as well as the importance of communication and interaction to stimulate children's language development.